2020
DOI: 10.1115/1.4046571
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Friction, Anti-wear, and Extreme Pressure Properties of Different Grades of Polyalphaolefins With Functionalized Multi-walled Carbon Nanotubes as an Additive

Abstract: In the present investigation, the COOH-functionalized multi-walled carbon nanotubes (MWCNTs) having an outer diameter of 20–30 nm and length 1−2 μm were dispersed in four different grades of polyalphaolefins (PAOs; i.e., PAO 4, PAO 6, PAO 40, and PAO 100) at various concentrations (0.025, 0.05, 0.075, 0.10, and 0.15 wt%) to evaluate friction, anti-wear, and extreme pressure properties. The tribological test was conducted as per ASTM standard using four-ball tester. The test results showed that with the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…At an optimum concentration, MWCNTs can easily get deposited into the grooves and valleys of rubbing surfaces and provides the effective rolling and mending effect; therefore, COF has decreased significantly. Although the presence of higher concentrations of the additive may develop large cluster due to aggregation of nanotubes which may diminish the rolling effect, consequently, it may cause ploughing action on the base metal due to hard and brittle nature of MWCNTs and introduces higher COF 25 .…”
Section: Tribological Performance Of Nanolubricants Friction Response Of Nanolubricantsmentioning
confidence: 99%
See 1 more Smart Citation
“…At an optimum concentration, MWCNTs can easily get deposited into the grooves and valleys of rubbing surfaces and provides the effective rolling and mending effect; therefore, COF has decreased significantly. Although the presence of higher concentrations of the additive may develop large cluster due to aggregation of nanotubes which may diminish the rolling effect, consequently, it may cause ploughing action on the base metal due to hard and brittle nature of MWCNTs and introduces higher COF 25 .…”
Section: Tribological Performance Of Nanolubricants Friction Response Of Nanolubricantsmentioning
confidence: 99%
“…16,17,19,21 From the above discussion, it is clear that limited research work is reported on the tribological properties of MWCNTs in PAO oils. [22][23][24][25] In the present work, varying fractions (0.025-0.15 wt.%) of COOH-functionalized MWCNTs was blended in three different grades of PAOs (PAO 4, PAO 6 and PAO 40) to develop nanolubricants. Taguchi's robust design method was used to analyse the influences of applied load, sliding velocity, the kinematic viscosity of PAOs and concentration of MWCNTs on the tribological performance of nanolubricants.…”
Section: Introductionmentioning
confidence: 99%
“…14 Similarly, in the presence of functionalized MWCNTs, the lubrication behaviour of PAO 4 and PAO 6 was significantly improved. 15,16 Due to their relatively low hardness, good resistance to thermal and chemical attack, high melting point and hexagonal crystal structure, the rare earth compound-based nanoparticles demonstrated significant potential as an additive in various lubricating oils to reduce friction and wear. Lanthanum trifluoride (LaF 3 ), a rare earth compound-based nanoparticle, has demonstrated outstanding tribological performance in lubricating oil and grease, as well as coatings.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the friction and wear qualities of the manufactured grease, a tribological test setup of four balls was employed. For grease containing Multi-Walled Carbon Nanotube, the wear scar width and friction coefficient were reduced by 25% and 60%, respectively [25]. Multi-Walled Carbon Nanotube with a length of 1-2 µm and an outer diameter of 20-30 nm were disseminated in four distinct classes of poly alpha olefins at varied concentrations to test friction, anti-wear, and severe pressure characteristics.…”
Section: Introductionmentioning
confidence: 99%